2001
DOI: 10.1002/pen.10921
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 welding of laminated linear low density polyethylene films

Abstract: Supercritical carbon dioxide (SC CO2) is used as a reversible plasticizing agent to promote solvent welding in highly oriented LLDPE films. These films are laid up in a quasi‐Isotropic fashion to enhance material properties in all directions. It is shown tht, after processing, the oriented morphology and crystallinity are effectively unchanged. These laminated films are investigated both physically and mechanically. The mechanical strength of laminate interfaces is tested using a T‐Peel test. Tensile propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…The detailed experiments can be found in Caskey and Lesser. 215 The authors reported a homogeneous morphology, which was aided by sc-CO 2 , in the intercalated nanocomposites containing as high as 40 wt% of OMLS. At this loading, only a 50% increase in modulus was observed.…”
Section: Nanocomposite Synthesis With the Aid Of Sc-comentioning
confidence: 98%
“…The detailed experiments can be found in Caskey and Lesser. 215 The authors reported a homogeneous morphology, which was aided by sc-CO 2 , in the intercalated nanocomposites containing as high as 40 wt% of OMLS. At this loading, only a 50% increase in modulus was observed.…”
Section: Nanocomposite Synthesis With the Aid Of Sc-comentioning
confidence: 98%
“…Polymers, such as polyethylene (PE), can be reversibly plasticized with CO 2 to promote solvent welding for producing laminated linear low-density polyethylene films [3]. In polymer processing, CO 2 is being used as a physical blowing agent in which microcellular foams can be formed that have fine characteristics (cell sizes < 10 m) that provides high performance products [1].…”
Section: Introductionmentioning
confidence: 99%
“…The details of this experimental apparatus have been discussed elsewhere, 13 but for thoroughness, the main points will be reiterated here. The mold is mounted in a PHI 40,000 lb hydraulic press.…”
Section: Methodsmentioning
confidence: 99%